Crafting Multimedia Text of Griya Kain Tuan Kentang as the Gift Shop in Palembang - Syafira Herliana; Nian Masna Evawati; Koryati (Politeknik Negeri Sriwijaya, 2025)
ABSTRACT: This research presents crafting multimedia text containing information about Griya Kain Tuan kentang as the gift shop in Palembang. The purpose of this research is to find how to craft the multimedia text of Griya Kain Tuan Kentang as the gift shop in Palembang by applying the steps for crafting multimedia text. The writers used the Research and Development method modified by Sukmadinata (2005) to achieve the purpose. The result shows that there are three steps to craft the multimedia text of Griya Kain Tuan Kentang as the gift shop in Palembang. The steps are preliminary study, model development, and final product testing. Based on the result, the multimedia text consists of the profile of Griya Kain Tuan Kentang, the history of Griya Kain Tuan Kentang, the kinds of products sold in Griya Kain Tuan Kentang, the range of prices, and the website or social media. Keywords: Crafting, Multimedia Text, Griya Kain Tuan Kentang, Gift Shop